Promoting hydrolysis of apple pomace by pectinase and cellulase to produce microbial oils using engineered Yarrowia lipolytica. (July 2019) - Liu, Liang; You, Yina; Deng, Hong; Guo, Yurong; Meng, Yonghong
Abstract: The low hydrolysis rate limits fermentable sugar production from apple pomace. Thus, efficient enzymatic hydrolysis techniques are critical. In this research, the release rate of galacturonic acid, the major monomer ingredient of pectin, achieved 9.23% by adding 0.05% pectinase to remove pectin which impedes the contact between cellulose and cellulase. Galacturonic acid was removed to facilitate the fermentation of Yarrowia lipolytica which could not utilize galacturonic acid. After optimization of cellulase hydrolysis parameters by response surface methodology, a maximum fermentable sugar yield of 67.54 ± 1.45% was obtained. The sugar was fermented using engineered strain Yarrowia lipolytica po1f ( pex10 − mfe − leu + ), with a maximum lipid yield of 25.8 g L −1 . The microbial oils yield from apple pomace hydrolyzate was higher than that from glucose because some pomace hydrolysate components (such as xylose) can be metabolized through the phosphoketolase reaction to produce more acetyl-CoA. Graphical abstract: Image 1 Highlights: Fermentable sugars from apple pomace are better for the production of microbial oils than glucose. Pectinase can accelerate the hydrolysis of pectin. Removal of galacturonic acid is more conducive to the fermentation by Yarrowia lipolytica. Optimization of cellulase hydrolysis conditions results in the highest fermentable sugar yield.